Numerical Simulation of the Effect of Flow Velocity and Inlet Position on the Pressure Drop in the Exhaust Manifold - Maretha Unique Reinauli Turangan (Indonesian Journal of Maritime Technology, 2023)
The exhaust manifold, also known as the exhaust header, is an important channel in the combustion chamber of a car. The exhaust manifold's role is to collect exhaust gas from various exhaust channels and direct it to the catalyst and car exhaust muffler for filtering. This research was conducted to see the pressure loss in the exhaust manifold at different speed conditions and different inlet positions on an engine with 4 cylinders. The speed variations used were 0.4, 0.6 and 0.8 m/s while the inlet position variations used were 1 and 3 and 2 and 4. The method used was numerical simulation. Geometry is created in the CAD software, then proceed with creating a mesh and setting boundary conditions. The results obtained show that the greater the flow rate, the greater the pressure drop. Based on the inlet position, positions 2 and 4 tend to have a greater pressure drop than positions 1 and 3 at each of the same speed. The largest pressure drop is 1.5438 Pa at a speed of 0.8 m/s with inlet channels 2 and 4.